Comparison of Chelex®-100 with two solid phase DNA extraction techniques. (December 2015) - Idris, B.; Goodwin, W.
Abstract: In the Ras Al Khaimah DNA Forensic Unit Chelex ® -100 is used when processing biological evidence. However, in many laboratories solid phase extraction techniques have gained popularity. Before changing methodology we wanted to compare the performance of two commonly used methods, the QIAamp ® DNA Investigator Kit (Qiagen, Germany) and the PrepFiler™ lysis buffer using the AutoMate Express™ System (Applied Biosystems). Fresh samples of blood, semen and saliva were placed onto cotton swabs and air-dried before extraction. Evaluation was based on the extracted DNA quantity and quality using real-time quantification (Quantifiler ® Human, Applied Biosystems). Additional criteria such as consistency, ease of use and cost efficiency were also considered. All extraction methods yielded good quality DNA with an IPC value between 27C t and 29C t with the exception of the Chelex ® -100 method when blood samples were processed. One-step analysis of variance showed significant differences in the quantity of DNA recovered between the methods tested ( p  = 0.0003 for blood, p  = 6.83e −5 for semen and p  = 0.002 for saliva). Chelex ® -100 gave the highest yield for semen and saliva and the AutoMate Express™ gave the highest yield when processing blood. Although QIAamp ® DNA Investigator gave lower yields it did produce the most consistent results, with little variation between extracts. Overall the AutoMate Express™ was the most favorable method tested; however Chelex ® -100 is a much cheaper alternative, which does not compromise on DNA yield and in practice rarely suffers from inhibition when processing routine casework.